The Easy to learn to crochet in just one day - American School of Needlework (Berne, IN DRG Pub, 2006)
This book teaches the basics of crochet in just eight hours. Includes easy-to-follow instructions illustrated with large step-by-step diagrams
Needlecrafts
1
Keywords: Handicrafts